2012
DOI: 10.1371/journal.pone.0042483
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nuclear Localization and Potential Function of Insulin-Like Growth Factor-1 Receptor/Insulin Receptor Hybrid in Corneal Epithelial Cells

Abstract: BackgroundType I insulin-like growth factor receptor (IGF-1R) and insulin receptor (INSR) are highly homologous molecules, which can heterodimerize to form an IGF-1R/INSR hybrid (Hybrid-R). The presence and biological significance of the Hybrid-R in human corneal epithelium has not yet been established. In addition, while nuclear localization of IGF-1R was recently reported in cancer cells and human corneal epithelial cells, the function and profile of nuclear IGF-1R is unknown. In this study, we characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 41 publications
9
41
0
Order By: Relevance
“…Nuclear internalization of cytokine receptors has been associated with cellular proliferation and, in most cases, to cancer (Aleksic et al 2010, Wang et al 2010, Wang & Hung 2012, Wu et al 2012). According to Conway-Campbell et al (2008), nuclear GHR is involved in transcriptional regulation, exhibiting many proprieties normally associated with transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear internalization of cytokine receptors has been associated with cellular proliferation and, in most cases, to cancer (Aleksic et al 2010, Wang et al 2010, Wang & Hung 2012, Wu et al 2012). According to Conway-Campbell et al (2008), nuclear GHR is involved in transcriptional regulation, exhibiting many proprieties normally associated with transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently this assay was also used to investigate the role of GH and IGF-I on testosterone on the androgen-responsive muscle (Serra et al, 2011) and the determination of nuclear localization and protein function of IGF-I/insulin receptor hybrids in corneal epithelial cells (Wu et al, 2012). This convenient assay that requires no wash steps and lends itself to automation seems to be the future with regard to the use of nucleic acid dyes for measurement of cell proliferation.…”
Section: Assays Involving Nucleic Acid Dye Incorporationmentioning
confidence: 99%
“…Our laboratory has been the first to identify the presence of the Hybrid-R in the corneal epithelium (Figure 10). 18 Importantly, studies using gene knockdown techniques have demonstrated preferential Hybrid-R formation compared to classical IGF-1R or INSR formation in corneal epithelial cells, underscoring the significance of this receptor in ocular surface biology.…”
Section: Mechanisms Of Corneal Epithelial Maintenance: Understanding mentioning
confidence: 99%
“…First, the Hybrid-R is present in the nucleus of corneal epithelial cells. 18 The presence of the Hybrid-R in the nucleus, where it interacts with DNA, means that it functions to regulate gene expression. Using state-of-art chromatin immunoprecipitation-DNA sequencing technology (ChIP-seq), we have been able to identify potential genes from enriched genomic DNA sequences that are targeted by the IGF-1R/INSR Hybrid-R (Table 1).…”
Section: Mechanisms Of Corneal Epithelial Maintenance: Understanding mentioning
confidence: 99%
See 1 more Smart Citation